2019
DOI: 10.1111/1744-7941.12245
|View full text |Cite
|
Sign up to set email alerts
|

‘Are we there yet?’ Australian HR professionals and the Fourth Industrial Revolution

Abstract: Although still in its early stages, the Fourth Industrial Revolution (FIR), which involves a broad range of artificial intelligence, robotics and machine learning technologies, will fundamentally change the way many of us work and relate to one another. Driven by technology, this transformation presents a range of challenges, as well as opportunities, where we might expect Human Resource (HR) professionals would lead the way. However, little is currently known in relation to how prepared HR professionals in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 10 publications
1
31
0
1
Order By: Relevance
“…In the area of interaction between different functions of organizations (executive efficiency) an increased productivity as well as effectiveness across the organization [36] is also assumed. In a survey conducted by Nankervis et al N = 250 company representatives indicated that they expected work performance to improve, productivity to increase, as well as employees to be well supported when using AI-applications, but that they were not yet planning to use this technology in the near future [37]. In the meta-analysis by Hirsch, it is emphasized that some applications of AI-technologies are perceived suspiciously to alarmingly on the part of employees.…”
Section: Literature Results For Levels Six and Sevenmentioning
confidence: 99%
“…In the area of interaction between different functions of organizations (executive efficiency) an increased productivity as well as effectiveness across the organization [36] is also assumed. In a survey conducted by Nankervis et al N = 250 company representatives indicated that they expected work performance to improve, productivity to increase, as well as employees to be well supported when using AI-applications, but that they were not yet planning to use this technology in the near future [37]. In the meta-analysis by Hirsch, it is emphasized that some applications of AI-technologies are perceived suspiciously to alarmingly on the part of employees.…”
Section: Literature Results For Levels Six and Sevenmentioning
confidence: 99%
“…At the same time, HR analytics is the biggest weakness of the organizations surveyed. The study conducted by Nankervis et al (2019) states that big data (15%), cloud technology (10%) and mobile technologies (8%) are not so popular and not likely to be actively used by HR practitioners in their daily work in the future. In particular, it leads to the need to develop greater awareness of HR professionals about the potential of current technologies and increase their motivation for developing new competencies.…”
Section: Discussionmentioning
confidence: 99%
“…When developing and setting goals, you can use the concept of MBO (Management by Objectives) -management by goals, founded by Peter Drucker. The peculiarity of the MBO concept is that the goals are not just "descending from top to bottom" -they are developed jointly by the boss and the subordinate [6]. During the discussions, personal goals are developed for each employee.…”
Section: Key Features Of the Skillaz Systemmentioning
confidence: 99%
“…The style of online business communication tends to change from more formal to less formal, which leads to a reduction in psychological distance. And in the case of a remote form of control, the psychological distance is maximum [6]. To deformalize communication, one should partially add personal correspondence.…”
Section: Key Features Of the Skillaz Systemmentioning
confidence: 99%